Participating CPTPP: Opportunities and Challenges for Vietnam’s Exports of Goods - Thi Oanh, Nguyen (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2019)
CPTPP is a new generation Free Trade Agreement (FTA) and a large-scale multilateral agreement adopted by Vietnam on January 14, 2019. Although it has a new face, the contents of the previous TPP remain in the CPTPP. The only difference in the CPTPP compared to the TPP is that there will be some commitments of postponement and unenforcement. This paper analyzes some of the contents committed to in the CPTPP that may affect Vietnam's export sector, and the opportunities and challenges for Vietnamese exports. This paper then makes some recommendations for the Vietnamese government and enterprises to further expand the scale of, and increase in export turnover.